Study on the Characteristics of CO2 Displacing Non-Newtonian Fluids - Yu-Ting Wu; Sung-Ki Lyu; Zhen Qin; Yanjun Qin; Hua Qiao; Bing Li (Lubricants)
CO2 displacement is a key technique that was examined through numerical methods in a 3D Hele–Shaw cell, with CO2 as the displacing phase and shear-thinning fluids as the displaced phase. Without interfacial tension effects, the displacement shows branching patterns forming two vertically symmetric fingers, regardless of whether the displacing fluid is air or CO2. Under CO2 displacement, viscous fingering propagates farther and achieves higher displacement efficiency than air. Compared with air displacement, the finger advancing distance increases by 0.0035 m, and the displacement efficiency is 15.2% higher than that of air displacement. Shear-thinning behavior significantly influences the process; stronger shear thinning enhances interfacial stability and suppresses fingering. As the power-law index n increases (reducing shear thinning), the fingering length extends. Variations in interfacial tension reveal it notably affects fingering initiation and velocity in CO2 displacement of non-Newtonian fluids, but has a weaker impact on fingering formation. Interfacial tension suppresses short-wavelength perturbations, critical to interface stability, jet breakup, and flows, informing applications like foam-assisted oil recovery and microfluidics.